{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

mid_ans_F02

# mid_ans_F02 - p 1 = e 1 λθ − 1 ∆ m 1(d Thus the...

This preview shows pages 1–4. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Midterm Exam’s Answer Key University of California at Berkeley Econ 202A, Macro Theory Fall 2002 George Akerlof, Andrea De Michelis October 29, 2002 1. Shapiro-Stiglitz The investor solves: ( p H = 10 + 1 / 2 1 . 25 p L + 1 / 2 1 . 25 p H p L = 0 + 1 / 4 1 . 25 p H + 3 / 4 1 . 25 p L The solution is: p H = 25 . 0 , p L = 12 . 5 . Thus, a risk neutral investor is willing to pay no more than \$25. Note: if one assumes that fundamental asset equation is of the form interest rate time asset value equals fl ow bene fi ts plus expected (not discounted) capital gains, then p H is \$20. 2. Near-rationality (a) p 0 = arg max p p ( m 0 p p ) p 0 = p 0 = m 0 since in equilibrium p p . (b) p 1 = arg max p p ( m 1 p p 0 ) = arg max p p ( m 0 + ε p m 0 ) p 1 = m 0 (1 + . 5 ε ) Thus, by not reoptimizing the fi rm looses p 1 q 1 ( p 1 ) p 0 q 1 ( p 0 ) = . 25 ε 2 m 2 0 (c) Yes, it is near-rational because the loss is of an order of magnitude smaller than the shock. 3. Exchange Rates (a) Using the LM equation: p 0 = m 0 φ y + λ r . (b) Thus, p 1 = m 1 φ y + λ r = p 0 + m 1 . (c) Recall that in equilibrium: e t e = ( λθ ) 1 ( p t p ) . Thus, e 0 = e 1 ( λθ ) 1 ( p
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: p 1 ) = e 1 + ( λθ ) − 1 ∆ m 1 . (d) Thus, the exchange has to overshoot by: e − e 1 = ( λθ ) − 1 ∆ m 1 . 4. Consumption The Euler condition for the problem is: u ( c t ) = E t u ( c t +1 ) , or since utility is quadratic and so marginal utility is linear: u ( c t ) = u ( E t c t +1 ) . (a) Thus, 1 − ac 1 = 1 − bE 1 c 2 = 1 − dE 1 c 3 , or E 1 c 2 = a b c 1 and E 1 c 3 = a d c 1 . When she plans consumption in period 1, her expected income is 3 Y , she sets c 1 so that c 1 + a b c 1 + a d c 1 = 3 Y ⇒ c ∗ 1 = 3 bd bd + ab + ad Y . (b) When she plans consumption in period 2, her expected income is 3 Y + ε 1 − c 1 , she sets c 2 so that c 2 + b d c ∗ 1 = 3 Y + ε 1 − c ∗ 1 ⇒ c ∗ 2 = 3 ad bd + ab + ad Y + d d + b ε 1 . 1...
View Full Document

{[ snackBarMessage ]}